Complications after Thyroidectomy; a Comparison Among Seven Different Surgical Procedures and the Impact of Central Compartment Lymph Nodes Sampling: a Cohort Study - Mismar , Ayman; Aladaileh, Mohammad; Obeidat, Firas; Al-Rawashdeh, Baeth Moh’d; Alimoglu , Orhan; Albsoul, Nader (Jordan Medical Journal, 2024)
Introduction: Thyroid nodules are commonly encountered in medical practice. The relation between the magnitude of thyroid surgery and its complications is not settled. Objectives: Our aim is to examine the incidence of recurrent laryngeal nerve injury and hypoparathyroidism after thyroid surgery in different thyroid procedures including local lymph nodes control. Methods: The records of 345 patients who underwent thyroidectomy at the Jordan University Hospital from January 2010 to December 2016 were reviewed. They were divided into seven groups (total thyroidectomy, near-total thyroidectomy, hemithyroidectomy, completion thyroidectomy, redo surgery, hemithyroidectomy with completion, and near-total thyroidectomy with completion). A comparison among the groups was done. Ninety-one patients who underwent central lymph nodes biopsy were identified. They were divided into three groups (pre-tracheal lymph nodes excision, central neck dissection, and central neck sampling) and then compared. Results: Transient hypocalcemia was significantly higher with total thyroidectomy in comparison to near-total thyroidectomy and hemithyroidectomy with or without completion. All groups were comparable regarding permanent hypocalcemia and recurrent laryngeal nerve palsy. No significant relationship between the type of dissection and complication rate was found. Conclusion: Near-total thyroidectomy is a safe alternative to total thyroidectomy with a lower early complication rate. Redo surgery and central dissection are not associated with higher morbidity.